Captain Carey U.S.A. [videorecording (DVD)] - Leisen, Mitchell, 1898-1972; Ladd, Alan; Hendrix, Wanda, 1928-1981; Albrand, Martha (Olive Films, 2012)
A former OSS operative who returns to Italy after the war to avenge the death of resistance worker Giulia, but only to find out that his 'deceased' lover is not only still alive, but also the wife of a powerful Italian baron. Carey decides to stick around, hoping to flush out the traitor who'd caused the wartime deaths of several of his OSS colleagues and resistance fighters.